2014
DOI: 10.1073/pnas.1320850111
|View full text |Cite
|
Sign up to set email alerts
|

Lysine deacetylase inhibition prevents diabetes by chromatin-independent immunoregulation and β-cell protection

Abstract: Type 1 diabetes is due to destruction of pancreatic β-cells. Lysine deacetylase inhibitors (KDACi) protect β-cells from inflammatory destruction in vitro and are promising immunomodulators. Here we demonstrate that the clinically well-tolerated KDACi vorinostat and givinostat revert diabetes in the nonobese diabetic (NOD) mouse model of type 1 diabetes and counteract inflammatory target cell damage by a mechanism of action consistent with transcription factor-rather than global chromatin-hyperacetylation. Wean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 35 publications
1
51
3
Order By: Relevance
“…In vitro, ITF2357 at 62.5 and 125 nM reduced cytokine-induced toxicity in rat and mouse beta cells (17,41). In the non-obese diabetic mouse model of Type 1 diabetes, ITF2357 added to the drinking water prevented the spontaneous development of diabetes (6). The daily dose of ITF2357 in that study was calculated at 1 mg/kg.…”
Section: Volume 290 • Number 4 • January 23 2015mentioning
confidence: 94%
See 1 more Smart Citation
“…In vitro, ITF2357 at 62.5 and 125 nM reduced cytokine-induced toxicity in rat and mouse beta cells (17,41). In the non-obese diabetic mouse model of Type 1 diabetes, ITF2357 added to the drinking water prevented the spontaneous development of diabetes (6). The daily dose of ITF2357 in that study was calculated at 1 mg/kg.…”
Section: Volume 290 • Number 4 • January 23 2015mentioning
confidence: 94%
“…Although HDACs deacetylate the highly conserved N-terminal lysines on nuclear histones, HDACs also target cytosolic proteins, such as transcription factors and proteins, that regulate cell proliferation, migration, and death (4). HDAC inhibitors hyperacetylate signal transducers and activators of transcription (STAT) (5) and NFB, both of which are associated with decreased inflammation (6).…”
Section: Itf2357 (Generic Givinostat)mentioning
confidence: 99%
“…Additionally, HDACi prevent the development of virus-induced T1DM by the modulation of immune response during diabetes progression [56]. However, it has also been reported that vorinostat, an HDACi, protects β-cells and prevents diabetes progression by chromatin-independent mechanism [57].…”
Section: Review Khan and Jenamentioning
confidence: 99%
“…Recent studies have yielded evidence that suggests a significant role for vorinostat in the treatment or prevention of both T1DM and T2DM because of its HDACi effects. It has been associated with b cell protection when given as monotherapy and as adjunctive therapy [23,24], and reduction of renal complications in patients with DM.…”
Section: Vorinostatmentioning
confidence: 99%
“…Givinostat was shown to revert diabetes in the NOD mouse, and also to protect against the recurrence of autoimmune diabetes after treatment discontinuation. It was found to have proinflammatory cytokine-suppressing properties and to protect pancreatic b cells from inflammatory destruction and infiltration in vitro at nM concentrations [24]. Importantly, these effects were achieved with low doses of givinostat (nearly 100 times lower concentrations) than those needed to reduce tumor size in animals.…”
Section: Givinostatmentioning
confidence: 99%